Uma proposta de metodologia para o ensino de Física usando robótica de baixíssimo custo - Araujo, Alessandro Vinicius Pereira Rolim de (2013)
This paper presents methodology based on Lev Vigotsky`s social interactionist theory through investigative activities, which integrates the teaching of physics to robotics, directed to students of the Physics degree course, seeking to provide further training for future teachers. The method is organized through educational robotics workshops that addresses concepts of physics through the use of low-cost educational robots along with several activities. The methodology has been presented and discussed and put into practice afterwards in workshops so that these future teachers may be able to take robotics to their classroom. Students from the last and penultimate semester of the Physics degree course of the Federal Institute of Education, Science and Technology of Rio Grande do Norte, Caicó campus participated in this project